Effect of Continuous Care Model-based Intervention on the Care Burden of the Caregivers of Patients With Spinal Cord Injury - Ziba Sarcami; Hasan Naviporh; Fazlollah Amadi (نشریه پرستاری ایران)
Background & Aims The family caregivers of patients with spinal cord injury (SCI) suffer from physical, psychological, social, and economic problems, which are called care burdens. The continuous support of these caregivers can reduce their care burden. This study aims to investigate the effect of the continuous care model (CCM) on the care burden of the caregivers of patients with SCI. Materials & Methods This quasi-experimental study was conducted in the winter of 2021 on 94 caregivers of patients with SCI covered by the welfare organization of Kamyaran City. They were selected using a convenience sampling method and randomly divided into intervention and control groups. The collection tools were a demographic form and the Zarit care burden interview (ZBI). The intervention group received the CCM-based intervention as a home-visiting program individually or in group format for three months. The control group received the routine patient care program presented by the welfare organization. The data were analyzed in SPSS v.16 software using descriptive and inferential statistics. Results After the CCM-based intervention, there was a significant reduction in the care burden of caregivers in the intervention was observed (P<0.001), but the difference was not significant in the control group (P>0.05). Conclusion The CCM-based intervention is effective in reducing the care burden of the caregivers of patients with SCI. It is recommended that the intervention be used on the caregivers of patients with other chronic diseases.